Emerging Role of Endosomal Toll-Like Receptors in Rheumatoid Arthritis - Thwaites, Ryan; Chamberlain, Giselle; Sacre, Sandra (Frontiers in Immunology, 2014)
Toll-like receptors (TLRs) and their downstream signalling pathways have been comprehensively characterised in innate immunity. In addition to this function, these receptors have also been suggested to be involved in the pathogenesis of many autoimmune diseases, including rheumatoid arthritis (RA). Murine in vivo models and human in vitro tissue models of RA have provided a wealth of information on the potential activity of TLRs and components of the downstream signalling pathways. Whilst most early work investigated the cell surface TLRs, more recently the focus has moved to the endosomal TLRs 3, 7, 8 and 9. These receptors recognise endogenous and exogenous double-stranded RNA, single-stranded RNA and DNA. The development of therapeutics to inhibit the endosomal TLRs or components of their signalling cascades may represent a way to target inflammation upstream of cytokine production. This may allow for greater specificity than existing therapies including cytokine blockade. Here, we review the current information suggesting a role for the endosomal TLRs in RA pathogenesis and the efforts to target these receptors therapeutically.